The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c8cy00462e
|View full text |Cite
|
Sign up to set email alerts
|

Supported gold–nickel nano-alloy as a highly efficient catalyst in levulinic acid hydrogenation with formic acid as an internal hydrogen source

Abstract: The surface Au–Ni nano-alloy was very efficiently used for the first time for the hydrogenation of levulinic acid with formic acid as an internal hydrogen source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 85 publications
0
57
0
Order By: Relevance
“…Being a noble metal, desorption on AuNP surface is stabilizing and hydrogen is less strongly chemisorbed on AuNP surface making the hydrogenation reaction faster. 43,44 Moreover, Au atoms were reported to induce electronic effects on d electrons of Ni similar to the Au@Ni core-shell alloys 14,36 where catalytic reactivity depends on the combined electronic effect of two metal components. It was further concluded that Au atoms in the core of the Au@NiNPs induced an electronic effect on the local density of Ni d states via the presence of core Au atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Being a noble metal, desorption on AuNP surface is stabilizing and hydrogen is less strongly chemisorbed on AuNP surface making the hydrogenation reaction faster. 43,44 Moreover, Au atoms were reported to induce electronic effects on d electrons of Ni similar to the Au@Ni core-shell alloys 14,36 where catalytic reactivity depends on the combined electronic effect of two metal components. It was further concluded that Au atoms in the core of the Au@NiNPs induced an electronic effect on the local density of Ni d states via the presence of core Au atoms.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to Ag, another precious metal, Au, was also reported to serve as the doping metal with excellent properties for enhancing the activity of Ni‐based bimetallic catalysts used in the FA/LA catalytic system. Ni‐based catalysts doped with a small amount of Au have been developed as efficient bimetallic catalysts for the conversion of the FA/LA system (5 wt % total metal content, Au/Ni ratio of 1:4) . The Au‐Ni bimetallic catalysts were found to exhibit high activity owing to the formation of bimetallic alloys, which was strongly influenced by the preparation methods.…”
Section: Heterogeneous Catalystsmentioning
confidence: 97%
“…ii) Bimetallic catalysts have shown advantages in improving catalytic activity and stability in biomass upgrading processes, and have promising application prospects for the FA/LA catalytic system (see Section 3.1.3) . Also, compared with pure precious metal catalysts, the bimetallic catalysts with a combination of precious and nonprecious metals could potentially reduce the preparation costs.…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…These catalytic results suggest that Au and Ni are closely interacting, as it is further elaborated in the discussion part. To Table 2 Temperature and selectivities to products at 100% conversion of butadiene over Au (10) emphasize this point, a previous result from our group 8 showed that a mechanical mixture (50-50% in catalyst weigh) of monometallic Au/TiO 2 (1 wt%) and Ni/TiO 2 (0.2 wt%), i.e., corresponding to an Au/Ni atomic ratio of 1.7, exhibited the same catalytic behavior (activity and selectivity) as the monometallic Ni/TiO 2 sample. These results also suggest that to understand how the catalytic properties are modied by the addition of gold, the metal particle microstructure must be known.…”
Section: Reaction Of Hydrogenation Of 13-butadienementioning
confidence: 99%